THE INFLUENCE BETWEEN LEARNING MOTIVATION AND STUDENTS’ ATTENTION TOWARD MATHEMATICS LEARNING OUTCOME IN THE OF VIII GRADE STUDENTS SMP MUHAMMADIYAH 7 YOGYAKARTA - Fima Okta Abriyani; Uus Kusdinar (Universitas Ahmad Dahlan, 2017)
Student learning outcomes are determined by many factors. Allegedly students’ learning motivation and attention are several factors that affect students learning outcomes. This study aimed to determine whether there is a positive and significant influence between learning motivation and students’ attention toward mathematics learning outcomes in the first semester of VIII grade students SMP Muhammadiyah 7 Yogyakarta in the academic year of 2016/2017. The population in this research was the students of VIII grade in SMP Muhammadiyah 7 Yogyakarta in the academic year of 2016/2017, consisted of class VIII A, VIII B, VIII C, VIII D, VIII E, VIII F, VIII G totaling 234 students. Samples were taken from VIII B as the research sample class and with the random sampling technique. The writer uses a questionnaire method to collect the data of learning motivation, attention of students and the resulting learning of math. The research instrument: validity test, different power test, and reliability test. Test requirement analysis includes a test of normality, the test of independence, and a test of linearity. The writer uses product-moment correlation analysis and multiple linear regression analysis to analyze the data. The results showed that there was a significant and positive influence between learning motivation and the attention of students towards mathematics learning outcomes in students class VIII in even Semester of SMP Muhammadiyah 7 Yogyakarta in the academic year of 2016 / 2017. It is showed by Fcount Ftable is with R = and R2 = with , with SR = , and SR = , SE = and SE = .